Chemoselective Tertiary C−H Hydroxylation for Late‐Stage Functionalization with Mn(PDP)/Chloroacetic Acid Catalysis. Issue 2 (26th December 2019) - Chambers, Rachel K.; Zhao, Jinpeng; Delaney, Connor P.; White, M. Christina
Abstract: Aromatic and heterocyclic functionality are ubiquitous in pharmaceuticals. Herein, we disclose a new Mn(PDP) catalyst system using chloroacetic acid additive capable of chemoselectively oxidizing remote tertiary C( sp 3 )−H bonds in the presence of a broad range of aromatic and heterocyclic moieties. Although catalyst loadings can be lowered to 0.1 mol% under a Mn(PDP)/acetic acid system for aromatic and non‐basic nitrogen heterocycle substrates, the Mn(PDP)/chloroacetic acid system generally affords 10–15% higher isolated yields on these substrates and is uniquely effective for remote C( sp 3 )−H hydroxylations in substrates housing basic nitrogen heterocycles. The demonstrated ability to perform Mn(PDP)/chloroacetic acid C( sp 3 )−H oxidations in pharmaceutically relevant complex molecules on multi‐gram scales will facilitate drug discovery processes via late‐stage functionalization. Abstract :